Tick Intrastadial Feeding and Its Role on IgE Production in the Murine Model of Alpha-gal Syndrome: The Tick “Transmission” Hypothesis - Maldonado-Ruiz, L. Paulina; Boorgula, Gunavanthi D.; Kim, Donghun; Fleming, Sherry D.; Park, Yoonseong (Frontiers in Immunology, 2022)
Recent studies have provided strong evidence indicating that lone star tick bites are a cause of AGS (alpha-gal syndrome, also known as red meat allergy RMA) in humans. AGS is characterized by an increase in IgE antibody production against galactose-alpha-1,3-galactose (aGal), which is a common glycan found in mammalian tissue, except in Old World monkeys and humans. The main causative factor of AGS, the lone star tick (Amblyomma americanum), is broadly distributed throughout the east and midwest of the United States and is a vector of a wide range of human and animal pathogens. Our earlier glycomics study of the salivary glands of partially fed male and female ticks revealed relatively high levels of aGal epitopes. In this study, we found that partially fed males of A. americanum on bovine blood, which engage in multiple intrastadial feedings, carry a large amount of aGal in the salivary glands. In our current work, we aimed to test whether ticks mediate the transmission of the aGal sensitizer acquired from nonhuman blood to humans in the intrastadial host switch (referred to as the “transmission” hypothesis). To test this hypothesis, we used an alpha-galactosyltransferase knockout mutant mouse (aGT-KO) model system infested with ticks that were unfed or partially fed on bovine blood. Based on the levels of total IgE and specific IgG and IgE antibodies against aGal after tick feedings, aGT-KO mice significantly responded to tick feeding and injection of aGal (Galα1-3Galβ1-4GlcNAc) conjugated to human serum albumin or mouse serum albumin (aGal-HSA or aGal-MSA) by increasing total IgE and aGal-specific IgE levels compared to those in C57BL/6 control mice. All of the treatments of aGT-KO mice involving the feeding of partially fed and unfed ticks functioned as sensitizers that increased the levels of specific IgE against aGal, with large individual variations. The data in this study do not support the “transmission” component of AGS, although they confirmed that aGT-KO mice can be used as a model for RMA studies.